Spatial Vulnerability of Street Vendors in Aizawl City, India - Lalnghakmawia Thangluah; Benjamin L Saitluanga (Indonesian Journal of Geography, 2023)
Street vending is one of the most visible informal occupations and a notable source of income for the urban poor. Contrary to what is projected in urban planning models, informal sector proliferates in cities of the Global South due to the combined processes of increasing urbanisation and globalization. The present paper is an attempt to measure spatial vulnerability of street vendors in Aizawl City- one of the fastest growing hill cities in India. By using simple random sampling method, 400 street vendors from five prominent street markets were interviewed through scheduled questionnaire. The analysis shows that the socio-economic condition of street vendors and the environmental quality of street markets varies spatially and, low level of vulnerability is associated with presence of proper regulation and provision of basic infrastructures. It also examines how street vendors in the city negotiated, appropriated and adapted to remain in the informal sector and, lastly, it appraises the role of the local government and communities in the process of livelihood protection of street vendors.